Impact of electricity deregulation in the state of California. (April 2017) - Razeghi, Ghazal; Shaffer, Brendan; Samuelsen, Scott
Abstract: The electric industry started as a natural monopoly and was regulated to protect the customers from high prices. Electricity deregulation was expected to reduce prices by introducing competitive markets. Every country or state implementing deregulation has gone through a unique experience. In this paper, the impact of electricity deregulation in the state of California is addressed by first examining historical retail prices, and second by developing a model to estimate the grid marginal costs using historical data. Results show that, although some customers pay lower rates today, the average customer does not pay a lower rate due to deregulation. Moreover, the results of the modeling show that the wholesale prices realized were higher than the marginal cost associated with the grid. Impacts of improved grid management are discussed along with transmission investments, market operator start-up and operation costs, energy and environmental goals, advances in technology on electricity prices, and the impact of deregulation on these factors. Highlights: A model is developed to determine electricity grid marginal cost in CA. Estimated grid marginal costs are lower on average that actual market prices. There is little evidence that restructuring resulted in reduced retail prices in CA. Implementing improved grid management resulted in a reduction in market price in CA. Environmental goals and technological advances significantly impact grid efficiency.